1, 4, 7-Trimethyl-1, 4, 7-Triazacyclononane as a Low-Loading Catalyst: CuBr–tmtacn Catalysed Glaser reaction of Acetylenes. (June 2014) - Sun, Jian; Zhang, Hua-He; Wang, Jian-Qiang; Li, Jing-Hua
1, 4, 7-Trimethyl-1, 4, 7-triazacyclononane (tmtacn, a cyclic trident-ligand) has been developed as a facile and efficient catalyst for Cu-catalysed homocoupling of terminal alkynes at room temperature. A variety of 1, 3-diynes have been synthesised in excellent yields with a catalyst loading on a scale of 0.1–0.5 mol% CuBr–tmtacn.